The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.2139/ssrn.214428
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Exchange Rate Regimes: Deeds vs. Words

Abstract: Most of the empirical literature on the relative merits of alternative exchange rate regimes uses the IMF de jure classification based on the regime that governments claim to have, abstracting from the fact that many countries that in theory follow flexible regimes intervene in the exchange market to an extent that in practice makes them indistinguishable from fixed rate regimes, and vice versa. To address this problem, in this paper we construct a de facto classification of exchange rate regimes. Using cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 25 publications
3
188
0
1
Order By: Relevance
“…More generally, Reinhart and Rogoff (2004) point out a widespread mismatch between declared and de-facto exchange rate regimes. Levy-Yeyati and Sturzenegger (2000) confirm the general finding but group countries differently due to using another methodology. 15 After the collapse many observers have become more careful with interpreting Argentina's solution as a "real" currency board.…”
Section: Exchange Rates and Their Consequencessupporting
confidence: 84%
“…More generally, Reinhart and Rogoff (2004) point out a widespread mismatch between declared and de-facto exchange rate regimes. Levy-Yeyati and Sturzenegger (2000) confirm the general finding but group countries differently due to using another methodology. 15 After the collapse many observers have become more careful with interpreting Argentina's solution as a "real" currency board.…”
Section: Exchange Rates and Their Consequencessupporting
confidence: 84%
“…Until recently, the fact that the official and the de facto regimes are often different has largely been ignored in the literature. However, as Calvo and Reinhart (2000) and Levy-Yeyati and Sturzenegger (2000) have recently pointed out, discrepancies between the official and the de facto regimes are not uncommon in practice. De facto regimes may be characterized by more or less exchange rate volatility than expected on the basis of official regimes, and these discrepancies may last for substantial periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier paper (von Hagen and Zhou (2002)) we have shown that the official regime choices of these countries can be explained empirically on the basis of standard arguments from international macro economics. Here, we extend Levy-Yeyati and Sturzenegger's (2000) analysis to our sample. We show, first, that, similar to their findings in a sample of industrialized and developing countries, regime discrepancies are in fact quite common among the countries we consider.…”
Section: Introductionmentioning
confidence: 99%
“…countries by what they say they do and it has been the traditional approach of the IMF and authors like Gosh, Gulde and Wolf (2003). The latter approach, as described by Levy-Yeyati and Sturznegger (2005), start with the principle that countries often do not do what they say they do which may be because of their "fear of freedom" or lack of credibility. Most countries listed as having a floating exchange rate in fact intervene in the foreign exchange market frequently.…”
Section: Mundell-fleming Modelmentioning
confidence: 99%